Mother-daughter murder night : a novel - Simon, Nina (New York : Harper Large Print, 2023)
Nothing brings an estranged family together like a murder next door. Lana Rubicon finds herself trapped 300 miles north of the city, convalescing in a sleepy coastal town with her adult daughter Beth and teenage granddaughter Jack. Jack - tiny in stature but fiercely independent - stumbles upon a dead body while kayaking near their bungalow. Jack quickly becomes a suspect in the homicide investigation, and the Rubicon women are thrown into chaos.
Keywords: Murder -- Fiction; Murder -- Investigation -- Fiction; Dysfunctional families -- Fiction; Mothers and daughters -- Fiction; Businesswomen -- Fiction; Grandmothers -- Fiction; Elkhorn Slough (Calif.) -- Fiction; Los Angeles (Calif.) -- Fiction; California -- Fiction; Detective and mystery fiction; Domestic fiction; Large print books